2011
DOI: 10.1007/s13596-011-0016-4
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of doxorubicin activity on breast cancer cell lines by tangeretin through cell cycle modulation

Abstract: Tangeretin, shows cytotoxic effect on COLO 205 colon cancer cells. Combination of tangeretin with tamoxifen showed synergistic effect and increased the cancer cell sensitivity towards tamoxifen on T47D cells. However, the combination of tangeretin with chemotherapeutic agent doxorubicin on breast cancer cells have not been explored yet. Therefore, the aim of this research is to examine the improvement of cytotoxic effect of doxorubicin by tangeretin through cell death induction and cell cycle modulation on MCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…This supports our view that this natural compound in combination with Dox, a conventional breast cancer chemotherapeutic agent, is useful to enhance the drug antitumor activity reducing its active concentration and the adverse toxic effect. In particular, we found that the strongly synergistic combination of the two compounds in both cell lines, as evaluated by means of CalcuSyn software, induced an increase of apoptosis and a modulation of cell cycle through a decrease of g0/g1 and S phases and an increase of g2/M phase similarly to Dox, when individually used; in fact, Dox was able to arrest the MCF-7 and t47D breast cancer cell lines at g2/M phase (24). Different studies also have indicated that Dox-induced apoptosis is associated with two distinct apoptotic pathways, i.e., the extrinsic and mitochondrial or intrinsic pathways (19).…”
Section: Discussionmentioning
confidence: 91%
“…This supports our view that this natural compound in combination with Dox, a conventional breast cancer chemotherapeutic agent, is useful to enhance the drug antitumor activity reducing its active concentration and the adverse toxic effect. In particular, we found that the strongly synergistic combination of the two compounds in both cell lines, as evaluated by means of CalcuSyn software, induced an increase of apoptosis and a modulation of cell cycle through a decrease of g0/g1 and S phases and an increase of g2/M phase similarly to Dox, when individually used; in fact, Dox was able to arrest the MCF-7 and t47D breast cancer cell lines at g2/M phase (24). Different studies also have indicated that Dox-induced apoptosis is associated with two distinct apoptotic pathways, i.e., the extrinsic and mitochondrial or intrinsic pathways (19).…”
Section: Discussionmentioning
confidence: 91%
“…synergistic action of flavonoid, kaempferol or resveratrol along with the Dox. Previously, Docetaxel (anthracycline) loaded lipid nanocapsules have been shown to induce a higher percentage of G2/M arrest in MCF-7 cells than free docetaxel [34].It is also reported earlier that Dox alone or a flavonoid daidzein bring about G2/M arrest in MCF-7 and MDA-MB-453 cells respectively and induce apoptosis [35,36]. Though evidences on the induction of apoptosis by free Dox and also of pure flavonoids have been presented, there are no reports so far on cell cycle arrest by Dox conjugated AuNPs.…”
Section: Morphological Assessmentmentioning
confidence: 89%
“…P21 expression causes the inhibition of cell cycle in the G1 and S phases caused by the E/CDK2 and A/CDK2 cycling activity inhibitions. The impeding of the cell cycle in the G1 and S phases causes cancer cell apoptosis induction (Meiyanto, 2011). The synergism effect of EDCG+5 FU combination is presumed that EDCG can be inducted and it can improve 5 FU efficacy through cancer cell apoptosis intrinsic path.…”
Section: Discussionmentioning
confidence: 99%